Discovery of a non‐stereoselective cytochrome P450 catalyzing either 8α‐ or 8β‐hydroxylation of germacrene A acid from the Chinese medicinal plant, Inula hupehensis. (30th November 2017) - Gou, Junbo; Hao, Fuhua; Huang, Chongyang; Kwon, Moonhyuk; Chen, Fangfang; Li, Changfu; Liu, Chaoyang; Ro, Dae‐Kyun; Tang, Huiru; Zhang, Yansheng
Summary: Sesquiterpene lactones (STLs) are C15 terpenoid natural products with α‐methylene γ‐lactone moiety. A large proportion of STLs in Asteraceae species is derived from the central precursor germacrene A acid (GAA). Formation of the lactone rings depends on the regio‐(C6 or C8) and stereoselective (α‐ or β‐)hydroxylations of GAA, producing STLs with four distinct stereo‐configurations (12, 6α‐, 12, 6β‐, 12, 8α‐, and 12, 8β‐olide derivatives of GAA) in nature. Curiously, two configurations of STLs (C12, 8α and C12, 8β) are simultaneously present in the Chinese medicinal plant, Inula hupehensis . However, how these related yet distinct STL stereo‐isomers are co‐synthesized in I .  hupehensis remains unknown. Here, we describe the functional identification of the I .  hupehensis cytochrome P450 (CYP71BL6) that can catalyze the hydroxylation of GAA in either 8α‐ or 8β‐configuration, resulting in the synthesis of both 8α‐ and 8β‐hydroxyl GAAs. Of these two products, only 8α‐hydroxyl GAA spontaneously lactonizes to the C12, 8α‐STL while the 8β‐hydroxyl GAA remains stable without lactonization. Chemical structures of the C12, 8α‐STL, named inunolide, and 8β‐hydroxyl GAA were fully elucidated by nuclear magnetic resonance analysis and mass spectrometry. The CYP71BL6 displays 63–66% amino acid identity to the previously reported CYP71BL1/2 catalyzing GAA 6α‐ or 8β‐hydroxylation, indicating CYP71BL6 shares the same evolutionary lineage with other stereoselective cytochrome P450s, but catalyzes hydroxylation in a non‐stereoselective manner. We observed that the CYP71BL6 transcript abundance correlates closely to the accumulation of C12, 8‐STLs in I .  hupehensis . The identification of CYP71BL6 provides an insight into the biosynthesis of STLs in Asteraceae. Significance Statement: A unique P450, CYP71BL6, catalyzing either 8α‐ or 8β‐hydroxylation of germacrene A acid contributes to the biosynthesis of C12, 8‐ STLs in the Chinese medicinal plant, Inula hupuhensis .